Prenatal Diagnosis of Cardiac Diverticulum with Pericardial Effusion in the First Trimester of Pregnancy with Resolution after Early Pericardiocentesis - Raquel Garcia Rodriguez; Azahara Rodriguez Guedes; Raquel Garcia Delgado; Lourdes Roldan Gutierrez; Margarita Medina Castellano; Jose Angel Garcia Hernandez (Case Reports in Obstetrics and Gynecology)
Cardiac diverticulum is a rare anomaly, which may present in association with pericardial effusion. Only few cases diagnosed during fetal life have been published and only in 12 cases pericardiocentesis was made with good postnatal outcomes in 83% of the cases. In the first trimester of pregnancy only 6 cases were reported. We described the largest series of cases published. We describe a case of cardiac diverticulum complicated with pericardial effusion during the first trimester of pregnancy and resolved by intrauterine pericardiocentesis at 17 weeks of pregnancy. We made a systematic review of the literature with the cases reported of cardiac diverticulum, management, and outcomes.